The impact of language of the wodiq in religious discourse - محمد صكبان عبد السيد بلسم (Journal of College of Education, 2019)
One of the key is sues discussed in the policy is to look for signs of renewal in religious discourse as a functional of reform. The efforts of this research focus on the study of the bilateral relationship between renewal in religious dis course and the age of the globalization of the modern mark language. Either at specific religious level in one country, as in this research or at general level represented by political in formation ledge has been stimulated by technological advances and changes have become rapid an successive, creating crises that vary from one society to another. Because it requires the physical and technical abilities and capabilities are difficult to provide at present time. Religion is at the forefront of the systems that suffer from these crises and the search for reform requires a few percentages. How can the language of renewed religious discourse be channeled and which levels have priority in innovation? Dose the modern media language help to remove some of the rhetorical obstacles and answer these question? The source of new Infor motion methods and modern methods and anew apporoach to innovation is only scientific research and exploratory in the religious fields, scientific research became an indispensable necessity Therefore ,one of the desired objectives for preparing this research was to:1- Understand the meaning of religious renewal 2-Explain the relationship of religious renewal in the era of media globalization 3-Conbine religious renewal with modern media for provide scientific staff with scientific material 5-To assist media owners in diagnosing non-peaceful situations in the relationship, this is why the research is divided in to two sections; The first of it dealt with the meaning of religious renewal and its levels and included home, prison ,school or the second motivator. He dealt with the meaning of the media language and the modern media, in clouding television and the social network, then impact of the language of the media in the Friday sermon is an analytical model according to the fresh ness of rhetoric and conclusion the research results and recommendations reached.